2016
DOI: 10.1016/j.bpj.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Membrane Domain-Forming Properties of the Lipids of Borrelia burgdorferi

Abstract: Co-existing disordered and ordered (raft) membrane domains exist in Borrelia burgdorferi, the causative agent of Lyme disease. However, although B. burgdorferi contains cholesterol lipids, it lacks sphingolipids-a crucial component of rafts in eukaryotes. To define the principles of ordered lipid domain formation in Borrelia, the domain forming properties of vesicles composed of its three major lipids, acylated cholesteryl galactoside (ACGal), monogalactosyl diacyglycerol (MGalD), and phosphatidylcholine (PC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Previous studies have shown the presence of cholesterol‐lipid containing microdomains in B.burgdorferi in vitro and in vivo (LaRocca et al ., ; LaRocca et al ., ), and have evaluated the contribution of different Borrelia lipid components to domain formation (Huang et al ., ). The finding that there are raft‐associated proteins as well as cholesterol and cholesterol glycolipids in the IM led us to study whether rafts can also be formed from their lipids.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous studies have shown the presence of cholesterol‐lipid containing microdomains in B.burgdorferi in vitro and in vivo (LaRocca et al ., ; LaRocca et al ., ), and have evaluated the contribution of different Borrelia lipid components to domain formation (Huang et al ., ). The finding that there are raft‐associated proteins as well as cholesterol and cholesterol glycolipids in the IM led us to study whether rafts can also be formed from their lipids.…”
Section: Resultsmentioning
confidence: 97%
“…Lipids having unsaturated acyl chains (acyl chains containing double bonds) have a decreased ability to form ordered domains relative to those with saturated acyl chains (London, ). The saturation of acyl chains is important for the formation of tightly packed ordered domains in eukaryotic cells (London, ), and in B. burgdorferi (Huang et al ., ). Therefore, using 1 H NMR we measured the number of double bonds in the three major Borrelia lipid species: PC, ACGal and MGalD.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations